2007
DOI: 10.1638/1042-7260(2007)038[0269:cbihmt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Biochemistry in Healthy Manatees (Trichechus Manatus Latirostris)

Abstract: Florida manatees (Trichechus manatus latirostris) are endangered aquatic mammals living in coastal and riverine waterways of Florida and adjacent states. Serum or plasma biochemical analyses are important tools in evaluating the health of free-ranging and captive manatees. The purpose of this study was to measure diagnostically important analytes in the plasma of healthy manatees and to determine whether there was significant variation with respect to location (free-ranging versus captive), age class (small ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 9 publications
7
41
1
1
Order By: Relevance
“…Although Harvey et al (2007) measured serum chemistry analytes in plasma, their results corroborate with the ones of the present study: total globulins increase while phosphates decrease with age, and AST levels were higher in calves than in adults. Our study is the first to report serum chemistry values for T. m. manatus in Brazil, representing an important contribution for a better understanding of the importance of marine mammals' clinical laboratory medicine to Rehabilitation Centers such as CMA/ICMBio, especially the ones which held the animals under their care for long periods.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although Harvey et al (2007) measured serum chemistry analytes in plasma, their results corroborate with the ones of the present study: total globulins increase while phosphates decrease with age, and AST levels were higher in calves than in adults. Our study is the first to report serum chemistry values for T. m. manatus in Brazil, representing an important contribution for a better understanding of the importance of marine mammals' clinical laboratory medicine to Rehabilitation Centers such as CMA/ICMBio, especially the ones which held the animals under their care for long periods.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Silva et al (2007) reported serum chemistry values for captive Antillean manatee adults, not verifying differences between genders. Further studies performed by Harvey et al (2007) evaluated the effects location (free-ranging vs captive), age class (small calves, large calves, subadults, adults), and sex exert on blood parameters, verifying differences in blood exams of captive animals, suggesting that factors such as diet, stress, and temperature might account for some of these results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Plasma biochemistry profiles conducted at UFPL were performed on a Hitachi 911ℱ Chemistry Analyzer (Boerhinger Mannheim/Roche Applied Science, Indianapolis, Indiana, USA) using reagents and technique described elsewhere [27]. The biochemistry profile included the following blood analytes: glucose; blood urea nitrogen (BUN); creatinine; alkaline phosphatase (ALP); gamma-glutamyl transferase (GGT); cholesterol; total protein (TP); albumin (ALB); potassium; magnesium; chloride; sodium; calcium; phosphorous; total bilirubin; direct bilirubin; amylase; lipase; lactate dehydrogenase; creatinine kinase phosphokinase; serum amyloid A; and iron.…”
Section: Methodsmentioning
confidence: 99%
“…All manatees appeared clinically healthy based on physical examination and fat measurements. Complete blood count (CBC) and chemistry were mostly unremarkable based on previously established reference intervals for hematology and chemistry analytes in Florida manatees (Harvey et al 2007(Harvey et al , 2009). Prior to testing, samples collected from years 2011, 2012, and January 2013 were kept frozen at −80°C.…”
Section: Serologic Surveymentioning
confidence: 99%